Dissolved, Labile, and Total Particulate Trace Metal Dynamics on the Northeast Greenland Shelf. Issue 12 (28th November 2022) - Chen, Xue‐Gang; Krisch, Stephan; Al‐Hashem, Ali; Hopwood, Mark James; Rutgers van der Loeff, Michiel M.; Huhn, Oliver; Lodeiro, Pablo; Steffens, Tim; Achterberg, Eric P.
Abstract: We present high‐resolution profiles of dissolved, labile, and total particulate trace metals (TMs) on the Northeast Greenland shelf from GEOTRACES cruise GN05 in August 2016. Combined with radium isotopes, stable oxygen isotopes, and noble gas measurements, elemental distributions suggest that TM dynamics were mainly regulated by the mixing between North Atlantic‐derived Intermediate Water, enriched in labile particulate TMs (LpTMs), and Arctic surface waters, enriched in Siberian shelf‐derived dissolved TMs (dTMs; Co, Cu, Fe, Mn, and Ni) carried by the Transpolar Drift. These two distinct sources were delineated by salinity‐dependent variations of dTM and LpTM concentrations and the proportion of dTMs relative to the total dissolved and labile particulate ratios. Locally produced meltwater from the Nioghalvfjerdsbræ (79NG) glacier cavity, distinguished from other freshwater sources using helium excess, contributed a large pool of dTMs to the shelf inventory. Localized peaks in labile and total particulate Cd, Co, Fe, Mn, Ni, Cu, Al, V, and Ti in the cavity outflow, however, were not directly contributed by submarine melting. Instead, these particulate TMs were mainly supplied by the re‐suspension of cavity sediment particles. Currently, Arctic Ocean outflows are the most important source of dFe, dCu, and dNi on the shelf, while LpTMs and up to 60% of dMn and dCo are mainly supplied by subglacial discharge from the 79NG cavity. Therefore, changes in the cavity‐overturning dynamics of 79NG induced by glacial retreat, and alterations in the transport of Siberian shelf‐derived materials with the Transport Drift may shift the shelf dTM‐LpTM stoichiometry in the future. Plain Language Summary: Trace metals (TMs) including cobalt (Co), iron (Fe), manganese (Mn), copper (Cu), and nickel (Ni) are essential micronutrients for marine productivity. The Northeast Greenland shelf is a climatically sensitive region, influenced by both outflowing Arctic waters and local glacier melting. We lack knowledge on how these Arctic surface waters affect TM dynamics on the Greenland shelf and how climatic shifts may influence TM dynamics. Here, we distinguish local submarine meltwater from Arctic surface waters using distinct tracers; noble gases and radium isotopes. We show that the TM dynamics on the shelf are largely controlled by the intrusion of Arctic surface waters which creates a near‐surface plume of dissolved and labile particulate TMs. Conversely, submarine meltwater creates a subsurface plume enriched in dissolved TMs but depleted in particulate TMs, which is exported from underneath a floating ice tongue. In the future, increasing Arctic river discharge and local glacial melting may both significantly change shelf micronutrient ratios demonstrating downstream impacts of a changing cryosphere on marine biogeochemical cycles. Key Points: The overall dissolved and particulate trace metal (TM) dynamics were mainly regulated by the mixing with Arctic surface waters Resuspension of cavity sediments is a major localized source of labile and total particulate Cd, Co, Fe, Mn, Ni, Cu, Al, V, and Ti Whilst dissolved and particulate TMs are mostly coupled on the Greenland shelf, cavity outflow decouples both phases